Mould prevention strategies for library buildings in tropical climate / Suriani Ngah Abdul Wahab and Md Yusof Hamid - Suriani, Ngah Abdul Wahab; Md Yusof, Hamid (Universiti Teknologi MARA, Perak, 2018)
This paper presents mould prevention strategies that should be applied in the library buildings. Library constructed in tropical climatic conditions must be moisture controlled from fungi or mould growth on any potential material. In order to identify the magnitude and the causes for mould growth, comprehensive research was carried out within three libraries in Malaysia universities. Aspergillus, Penicillium, Stachybotrys's and fungal had been identified as a common mould growth found. Thus, the growth of mould on the building elements such as walls and floors carpets, books, air conditioning parts of the surrounding library areas will be inevitable unless prevention strategies applied. Four strategies have been identified as possible mould prevention strategies in the library building